Do electric vehicles need subsidies in the UK?. (February 2021) - Santos, Georgina; Rembalski, Sebastian
Abstract: We analyse the total cost of ownership of petrol, diesel, hybrid electric vehicles, plug-in hybrid electric vehicles and battery electric vehicles in the UK over 2017–2029. We do this for large, medium and small cars, under assumptions of 0%, 6%, 30% and 60% discount rates. We find that some electric car models from mass market brands are close to reaching cost parity with their petrol, diesel and hybrid counterparts, but subsidies would accelerate their uptake, especially for impatient consumers with high discount rates. Plug-in hybrid electric vehicles are not worth the effort because, although relatively low, their CO2 emissions are non-zero, and their purchase price is as high or even higher than that of battery electric vehicles. A subsidy of £4, 500 or an exemption from the 20% VAT, perhaps capped at £4, 500, would accelerate mass market penetration of battery electric vehicles in the UK. If decarbonising road transport were not as urgent as it is, the market for battery electric vehicles could be left to develop on its own, without government intervention. However, because the cost of batteries is not falling fast enough, subsidies are needed in the short term. Highlights: We analyse TCO of petrol and diesel cars, HEVs, PHEVs and BEVs in the UK over 2017-29. TCO are very sensitive to the car purchase price. We find that plug-in hybrid and battery electric cars need subsidies. Battery electric cars should be favoured in terms of subsidies.